2022
DOI: 10.1101/2022.02.27.481963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into the functioning of GMP synthetase: a two-subunit, allosterically regulated, ammonia tunnelling enzyme

Abstract: Guanosine 5'-monophosphate (GMP) synthetases, enzymes that catalyze the conversion of xanthosine 5'-monophosphate (XMP) to GMP are comprised of two different catalytic units, which are either two domains of a polypeptide chain or two subunits that associate to form a complex. The glutamine amidotransferase (GATase) unit hydrolyzes glutamine generating ammonia and the ATP pyrophosphatase (ATPPase) unit catalyzes the formation of AMP-XMP intermediate. The substrate-bound ATPPase allosterically activates GATase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Structural comparisons between four GMPS FunFams showed that the Lid region is differentially conserved between FunFams, supported by previous experiments 7,27,28 . In addition, sequence comparisons between GMPS FunFams exposed several residues within the Lid region that are differentially conserved, providing new insights into various modes by which the Lid region regulates Gln-hydrolysis and NH 3 -transportation.…”
Section: Substrate a + Atp → Substrate A-amp + Ppisupporting
confidence: 80%
See 4 more Smart Citations
“…Structural comparisons between four GMPS FunFams showed that the Lid region is differentially conserved between FunFams, supported by previous experiments 7,27,28 . In addition, sequence comparisons between GMPS FunFams exposed several residues within the Lid region that are differentially conserved, providing new insights into various modes by which the Lid region regulates Gln-hydrolysis and NH 3 -transportation.…”
Section: Substrate a + Atp → Substrate A-amp + Ppisupporting
confidence: 80%
“…Bacterial FunFam members not only share SDP residue conservation patterns with the Plasmodium GMPS (Table .3), but also possess the same MDA as the Plasmodium FunFam Although lacking the intrachain ATP-PPase-GATase interaction, the archaeal MDA is similar to the bacterial one (Figure .3a). The predicted archaeal GMPS complex with the GATase bound to the ATP-PPase subunit is similar to the unrotated Plasmodium GMPS 27 . Since archaeal GMPS FunFam have hydrophobic and aromatic residues conserved on SDPs 222, 370 and 415 similar to the Plasmodium GMPS FunFam (Table .3), the bound archaeal GATase subunit may undergo further rotation and activation like the Plasmodium GMPS 27 .…”
Section: Different Multidomain Architectures Reflect Different Modes ...mentioning
confidence: 73%
See 3 more Smart Citations